Interaction of hydrogen in carbon matrix with impurities of nickel. Effects of spin fluctuation - Gervasoni, Juana Luisa (2014)
This work aims to define general criteria to allow theoretical and experimental design of new materials with high hydrogen content, with a view to their potential application as moderators in reactors at high temperatures and hydrogen storage materials. To this end we study the effects of nickel impurities on the properties of pure carbon (slabs as well as nanoparticles and gels) in order to analyze the thermodynamical characteristics, and improve the behavior of alloys for Ni-metal hydride rechargeable batteries. These elements are chosen because they have a wide range of solubility of hydrogen, which from the technological point of view makes them important candidates in the search for new materials. Our results show that this kind of carbon material could be used as support for hydrogen storage improving the screening charge density and the density of available states, as analyzed by the authors in previous works.